Data Collection Survey on Forest Conservation in Mahavir Swami Wildlife Sanctuary for Addressing Climate Change - Lavania, Pankaj; Gupta, Garima; Kumar, Pavan; Singh, K.K.; Tiwari, Prabhat; Dobriyal, Manmohan; Pandey, A.K.; Srivastav, Manish (Hacquetia, 2024)
Tropical forest serves as an important pivotal role in terrestrial biological diversity. The tropical forest acts as munificence for the life forms living in the tropics, by providing habitat conditions and natural resources. Tree parameter measurement is an important part of forest resource monitoring. The Data Collection Survey on Forest Conservation aims to provide a comprehensive analysis of the current state of forests and evaluate the effectiveness of conservation efforts. This survey integrates advanced data collection methods, including remote sensing and Geographic Information Systems (GIS), to monitor forest health, biodiversity, and threats. Key findings highlight critical areas of biodiversity that require targeted conservation, the pervasive threats from illegal logging and climate change, and the significance of community involvement in conservation initiatives. This study makes an attempt to data collection surveying methods to assess forest management in Mahavir Swami Wildlife Sanctuary (MSWS), Lalitpur, UP, India, using Sentinel-2A sensor data. We selected tree samples from thirty transects in MSWS through random sampling. A method of collecting tree measurement factors based on height and DBH with a variety of high-precision methods is proposed. The data collection survey used in this study can help forest managers, environmentalist, and conservationist for formulating policies for management of forest ecosystem at various scales.